Antibody response and risk factors for seropositivity in backyard poultry following mass vaccination against highly pathogenic avian influenza and Newcastle disease in Indonesia - McLaws, M.; Priyono, W.; Bett, Bernard K.; Al-Qamar, S.; Claassen, I.; Widiastuti, T.; Poole, Elizabeth J.; Schoonman, L.; Jost, Christine; Mariner, Jeffrey C. (Cambridge University Press, 2015)
A large-scale mass vaccination campaign was carried out in Java, Indonesia in an attempt to control outbreaks of highly pathogenic avian influenza (HPAI) in backyard flocks and commercial smallholder poultry. Sero-monitoring was conducted in mass vaccination and control areas to assess the proportion of the target population with antibodies against HPAI and Newcastle disease (ND). There were four rounds of vaccination, and samples were collected after each round resulting in a total of 27 293 samples. Sampling was performed irrespective of vaccination status. In the mass vaccination areas, 20–45% of poultry sampled had a positive titre to H5 after each round of vaccination, compared to 2–3% in the control group. In the HPAI + ND vaccination group, 12–25% of the population had positive ND titres, compared to 5–13% in the areas without ND vaccination. The level of seropositivity varied by district, age of the bird, and species (ducks vs. chickens).